Analisis Distribusi Cpo (Crude Palm Oil) di PT Pinago Utama Tbk Palembang - Linda Linda; Juhaini (Syntax Literate, 2023)
Distribution channel is an important factor in increasing production and sales in a company. Selection of the right distribution channel is the spearhead of a company's success. PT Pinago Utama Tbk is a company engaged in the oil palm and rubber plantations. In its production activities, PT Pinago Utama Tbk uses direct distribution channels. The purpose of this research is to overcome the distribution channel barriers at PT Pinago Utama Tbk in order to increase the company's production and sales and implement the solutions obtained to increase the company's production and sales. The research method used is a qualitative method through in-depth interviews (In-depth Interview). Data collection was carried out by interviewing company management and expert judgment. After that an analysis was made based on the results of the interviews conducted. Based on the results of interviews and SWOT analysis, it was found that the distribution channel has internal and external obstacles. Internal obstacles in the form of existing human resources, external obstacles come from third parties. Based on the analysis carried out, it is necessary to reshuffle the existing human resources at PT Pinago Utama Tbk and the need for communicative collaboration with third parties.